A Case of Acquired Anterior Scleral Staphyloma and Corneal Perforation After Pars Plana Vitrectomy and Treatment with Amniotic Membrane - Erdag, Murat; Canleblebici, Mehmet; Dal, Ali; Yıldırım, Hakan (My University, 2023)
This is a case report of a 26-year-old female patient who presented with poor vision due to a vitreous lens drop of her right e ye. The patient underwent pars plana vitrectomy. However, scleral fixation was postponed due to corneal edema. She presented to theclinic 2 months later with complaints of eye pain. The patient was found to have a corneal perforation and iris prolapse. Emergency surgery wasperformed, and after the iris tissue were repositioned, the corneal defect was sutured and an amniotic membrane was transplanted onto the defe ct. The corneal defect healed, and the anterior staphyloma did not progress. The patient’s underlying condition was suspected to be a congenital connective tis- sue disorder. Anterior staphyloma may develop after vitrectomy in patients with congenital tissue disease, and amniotic membrane closure may be preferred in these patients for better healing process.
Keywords: Anterior staphyloma; congenital connective tissue diseases; amniotic membrane; corneal perforation